Characteristics, risk factors and outcomes of Clostridium difficile infections in Greek Intensive Care Units. (August 2019) - Matthaiou, Dimitrios K.; Delga, Dimitra; Daganou, Maria; Koutsoukou, Antonia; Karabela, Niki; Mandragos, Konstantinos E.; Kalogeropoulou, Eleni; Dimopoulos, George
Abstract: Background: Clostridium difficile is one of the major causes of diarrhoea among critically ill patients and its prevalence increases exponentially in relation to the use of antibiotics and medical devices. We sought to investigate the incidence of C. difficile infection in Greek units, and identify potential risk factors related to C. difficile infection. Methods: A prospective multicenter cohort analysis of critically ill patients (3 ICUs from 1/1/2014 to 31/12/2014). Results: Among 970(100%) patients, 95(9.79%) with diarrhoea, were included. Their demographic, comorbidity and clinical characteristics were recorded on admission to the unit. The known predisposing factors for the infection were recorded and the diagnostic tests to confirm C. difficile were conducted, based on the current guidelines. The incidence of C. difficile infection was 1.3% (n = 13). All-cause mortality in patients with diarrhoea, C. difficile infection and attributable mortality in patients with C. difficile infection was 28%, 38.5% and 30.8% respectively. Sequential Organ Failure Assessment (SOFA) scores on admission were significantly lower and prior C. difficile infection was more common in patients with current C. difficile infection. Regarding other potential risk factors, no difference was found between groups. No factor was independently associated with C. difficile infection. Conclusions: C. difficile infection is low in Greek intensive care units, but remains a serious problem among the critically-ill. Mortality was similar to reports from other countries. No factor was independently associated with C. difficile infection.